Pendidikan Kebangsaan dalam Perspektif Al - Qur'an - Azzah Nor Laila (JASNA : Journal For Aswaja Studies, 2021)
AbstractProblems  of disunity  and less  of public  awareness  about the  sense of belonging in the  nation, often become  a  trigger  for  tension  and  disharmony  in  social  relations.  Both  within  the  scope  of  fellow religious people, as well as within a nation. To mediate this, the planting of a sense of belonging to the nation or education about nationality to the community is important as a solution. This paper aims to find  the  message  of  national  education  in  the  Qur'an.  Al-Qur'an  as  a  Muslim  holy  book  is  full  of educational values. This paper uses thematic methods and content analysis of the text of the Qur'anic verses  about  the  nation.  The  findings  of  national  education  in  the  perspective  of  the  Qur'an  are recommendations  to  uphold  the  equal  rights  of  citizens  in  a  nation.  The  importance  of  government cooperation with its people. The peace and tranquility of a country is essentially based on the attitude of its inhabitants, it is carried out by means of gratitude, use of voting rights, deliberation, courtesy and  honesty.  The  importance  of  introspection and evaluation.  Every citizen of the  country,  both the people and the authorities, must have a mistake. All residents should be aware and admit their mistakes, then correct and apologize to those who are judged and to the Forgiving.Keywords: education, nationality, Qur’an versesAbstrakProblem perpecahan serta kurangnya kesadaran masyarakat tentang sense of belonging pada bangsa, sering menjadi pemicu ketegangan serta disharmoni hubungan sosial. Baik dalam lingkup sesama umat beragama, maupun dalam suatu bangsa. Untuk menengahi hal itu, penanaman sense of belonging pada bangsa  atau  pendidikan  tentang  kebangsaan  pada  masyarakat  menjadi  hal  penting  sebagai  solusi. Tulisan ini bertujuan menemukan pesan pendidikan kebangsaan  dalam al-Qur’an. Al-Qur’an sebagai kitab suci umat Islam sarat dengan nilai-nilai pendidikan. Tulisan ini menggunakan metode tematik serta  content  analysis  terhadap  teks  ayat-ayat  al-Qur’an tentang bangsa. Hasil temuan pendidikan kebangsaan dalam perspektif al-Qur’an adalah anjuran menjunjung kesamaan hak warga dalam suatu bangsa.  Pentingnya  kerjasama  pemerintah  dengan  rakyatnya.  Kedamaian  dan  ketentraman  suatu negara   hakikatnya   didasarkan   pada   sikap   penduduknya,  diantarnya   dengan   cara   bersyukur, menggunakan hak suara, bermusyawarah, santun berpendapat dan jujur. Pentingnya introspeksi dan evaluasi. Setiap penduduk negara baik rakyat maupun penguasa pasti memiliki kesalahan. Hendaknya semua penduduk menyadari dan mengakui kesalahannya, kemudian memperbaiki dan memohon maaf kepada pihak yang didhalimi serta kepada Maha Pengampun.Keywords: pendidikan, kebangsaan, ayat al-Qur’an